Some Observations of the Behaviour of an Adverse Pressure Gradient Laminar Boundary Layer under Wake Impingement - Vasudevan Kanjirakkad (Fluids, 2021)
The problem of laminar to turbulent transition in a boundary layer flow subjected to an adverse pressure gradient is relevant to many engineering applications. Under such conditions, the initially laminar flow within the boundary layer can undergo separation and then become turbulent upon reattachment, as transition is triggered by instabilities within the separated shear layer. In turbomachinery blades with high loading, the transition mechanism is further complicated by the presence of periodic wake disturbances shed by blades that move relatively in the upstream flow. The paper reports an experimental study of the effect of wake disturbances generated upstream on the development of a laminar boundary layer over a flat plate imposed with an adverse pressure gradient that is typical of a highly loaded front-stage compressor blade. Detailed velocity measurements using a hotwire are performed along the plate and the results are analysed both in the time domain and the frequency domain. Description of the major features identified is provided and the leading mechanisms that trigger the transition process are identified to be a possible combination of amplified Tollmien–Schlichting waves and the roll-up of vortices due to the Kelvin–Helmholtz instability of the separated shear layer.